Virtual Surgical Planning and Piezoelectric Surgery in Tumor Extirpative Surgery Aimed at Inferior Alveolar Nerve Preservation - Eric L. Chung; Faizan Alawi; Anh D. Le; Rabie M. Shanti (Case Reports in Surgery)
A myriad of extirpative surgical protocols for the management of benign tumors of the jaws have been presented in the literature. Through significant advancements in computer-aided design and computer-aided manufacturing (CAD/CAM) technology and surgical instrumentation, today surgeons have at their disposal robust technology-driven techniques that are aimed at improving surgical outcomes. Our goal is to investigate the benefits of implementing virtual surgical planning (VSP) in conjunction with piezoelectric surgery (PES) to ensure success while minimizing the risk of complications during extirpation of tumors of the mandible. This case report describes the successful extirpation of an ossifying fibroma of the mandible in an adult patient using both VSP and PES.